The ATR-WEE1 kinase module inhibits the MAC complex to regulate replication stress response. Issue 3 (15th January 2021) - Wang, Lili; Zhan, Li; Zhao, Yan; Huang, Yongchi; Wu, Chong; Pan, Ting; Qin, Qi; Xu, Yiren; Deng, Zhiping; Li, Jing; Hu, Honghong; Xue, Shaowu; et al.
Abstract: DNA damage response is a fundamental mechanism to maintain genome stability. The ATR-WEE1 kinase module plays a central role in response to replication stress. Although the ATR-WEE1 pathway has been well studied in yeasts and animals, how ATR-WEE1 functions in plants remains unclear. Through a genetic screen for suppressors of the Arabidopsis atr mutant, we found that loss of function of PRL1, a core subunit of the evolutionarily conserved MAC complex involved in alternative splicing, suppresses the hypersensitivity of atr and wee1 to replication stress. Biochemical studies revealed that WEE1 directly interacts with and phosphorylates PRL1 at Serine 145, which promotes PRL1 ubiquitination and subsequent degradation. In line with the genetic and biochemical data, replication stress induces intron retention of cell cycle genes including CYCD1;1 and CYCD3;1, which is abolished in wee1 but restored in wee1 prl1 . Remarkably, co-expressing the coding sequences of CYCD1;1 and CYCD3;1 partially restores the root length and HU response in wee1 prl1 . These data suggested that the ATR-WEE1 module inhibits the MAC complex to regulate replication stress responses. Our study discovered PRL1 or the MAC complex as a key downstream regulator of the ATR-WEE1 module and revealed a novel cell cycle control mechanism.